2017
DOI: 10.1097/iae.0000000000001304
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreflective Retinal Spots in Normal and Diabetic Eyes

Abstract: Hyperreflective retinal spots ≤30 μm, reflectivity similar to nerve fiber layer, and absence of back shadowing may represent activated microglial cells; HRS >30 μm, reflectivity similar to retinal pigment epithelium-Bruch complex, presence of back shadowing, and location in the outer retina may represent hard exudate; HRS >30 μm, presence of back shadowing, and location in the inner retina may represent microaneurysms. These hypotheses may be tested in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 23 publications
0
65
1
1
Order By: Relevance
“… 28 These include HRS, visible on OCT, and considered the signs of activated microglial cells in the retina. 29 These HRS have peculiar features, such as dimension <3 0 μm, reflectivity similar to that of the nerve fiber layer, absence of back-shadowing, and location in both the inner and outer retina. 29 Previous studies have demonstrated a decrease in the number of HRS after treatment with both intravitreal dexamethasone and anti-VEGF drugs 23 , 30 , 31 ; however, no evidence has been reported so far regarding the effect of SMPL on HRS during long-term follow-up.…”
Section: Discussionmentioning
confidence: 98%
“… 28 These include HRS, visible on OCT, and considered the signs of activated microglial cells in the retina. 29 These HRS have peculiar features, such as dimension <3 0 μm, reflectivity similar to that of the nerve fiber layer, absence of back-shadowing, and location in both the inner and outer retina. 29 Previous studies have demonstrated a decrease in the number of HRS after treatment with both intravitreal dexamethasone and anti-VEGF drugs 23 , 30 , 31 ; however, no evidence has been reported so far regarding the effect of SMPL on HRS during long-term follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…One study recently evaluated characteristics of these hyperreflective “spots” and compared them with features on en face images. 7 They suggested that when larger than 30μm, these spots may represent hard exudate in the outer retina. For DME patients, Bolz et al suggests that HRM may represent subclinical extravasation of lipoproteins and/or proteins, secondary to breakdown of the blood retinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The study presented here further showed that morphological features like center-involving intraretinal hyperreflective material detected by SD-OCT may represent a negative predictive factor in the eyes with DME because the initially observed inferior VA of the eyes revealing intraretinal hyperreflective foci at baseline remained until the end of the follow-up period (0.39; 20/50 Snellen (SD = 0.25) versus 0.68; 20/63 Snellen (SD = 0.22), p =25, Table 3 ). Hyperreflective intraretinal spots define exudates as visible clinically and were described previously by Vujosevic et al [ 17 ]. Hyperreflective structures seen in SD-OCT correlated to hard exudates observed in biomicroscopy in our study.…”
Section: Discussionmentioning
confidence: 99%